Leasing Procedure of Fixed Assets in Budget Organizations and their Expenditure - Ganiyev Shakhriddin Vohidovich (Indonesian Journal of Public Policy Review, 2022)
Accounting for transactions related to the receipt and expenditure of rental income to budget organizations is one of the most pressing issues today. In this article we discuss what the leasing of fixed assets is and some peculiarities of these assets in budget organizations. We also describe what a lease agreement is and what are stated in this type of an agreement.